1994
DOI: 10.1071/ea9940395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of sowing on flowering in faba bean (Vicia faba)

Abstract: Sequential sowings of faba bean (Vicia faba) were conducted to examine the effect of sowing date and a vernalisation treatment on the phenology of a range of faba bean accessions. There was very little difference between accessions in the rate of germination. Delayed sowing increased the time to establishment, but the thermal time from sowing to emergence did not vary greatly. On average 208�C.day was required for emergence and the base temperature for germination was near 0�C for all accessions. The shortest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Broad bean is mostly grown under field conditions, but greenhouse environmental conditions may allow for an effective prevention of environmental unbalances [12]. Planting time is also crucial in Vicia faba management in order to maximize seed quality, as it is strictly matched to the growing environment and even affects the crop cycle in terms of possible occurrence of abiotic and/or biotic stresses [13].…”
Section: Introductionmentioning
confidence: 99%
“…Broad bean is mostly grown under field conditions, but greenhouse environmental conditions may allow for an effective prevention of environmental unbalances [12]. Planting time is also crucial in Vicia faba management in order to maximize seed quality, as it is strictly matched to the growing environment and even affects the crop cycle in terms of possible occurrence of abiotic and/or biotic stresses [13].…”
Section: Introductionmentioning
confidence: 99%
“…Italy is a major European producer, with a total area of 49,000 ha devoted to this crop in 2014 [1]. Faba bean is mostly grown under field conditions, but greenhouse culture allows for crop growth and productivity enhancement in mild climate areas with a rainy early spring season [2], as well as for plant protection against environmental unbalances [3]. Planting time is also crucial in faba bean management, as it affects the growth cycle in terms of possible occurrence of abiotic and/or biotic stresses [4].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the time to flowering decreases with a longer photoperiod as faba bean is a long-day plant (requires long days to flower), but day-neutral genotypes (that eventually flower regardless of photoperiod) and photoperiod unresponsive genotypes (that flower in the same amount of thermal time regardless of photoperiod) have also been identified (Evans 1959;Ellis et al 1990;McDonald et al 1994). Variation in response to ambient temperature has not been as comprehensively studied as response to photoperiod.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al (1990) reported that all faba bean genotypes require about the same amount of thermal time to flower (~1000 °C.d). McDonald et al (1994), however, observed variation in TTF in a wider range of genotypes, with one line flowering in as little as 611 °C.d. Vernalisation has been shown to decrease the time to flowering and variation in response to vernalisation has been observed in faba bean (Ellis et al 1988a;McDonald et al 1994), however, the occurrence of a true vernalisation response has been disputed (Ellis et al 1988b) and it is not covered in the present study -further mention of temperature refers to ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation